Goalkeepers put their money where the coach's mouth is: Knowing kickers' preferences enhances anticipation of football goalkeepers. Issue 5 (3rd September 2022) - Murta, Cristiano da Conceição Ferreira; Albuquerque, Maicon Rodrigues; Greco, Pablo Juan; Raab, Markus; Praça, Gibson Moreira
ABSTRACT: We investigated the influence of providing football goalkeepers with kicker's prior preferences on anticipation and gaze behaviour to explore the interaction of top-down and bottom-up cognitive processing. Forty participants (20 experienced goalkeepers and 20 novices) were asked to anticipate the direction of penalty kicks in three experimental conditions: without information (control situation), with correct information (congruent condition), and with wrong information (incongruent condition) on a kicker's prior preferences. An eye-tracking device was used to analyse fixations on areas of interest. The participants anticipated the direction of the kick in congruent situations better than in the other two conditions ( p = 0.001). Experienced goalkeepers were superior to novices in the incongruent and control conditions ( p = 0.001). In those conditions, experienced goalkeepers also fixated more ( p = 0.025) and longer ( p = 0.046) on the trunk, and longer on the hips ( p = 0.036), non-kicking leg ( p = 0.001), and kicking leg ( p = 0.001). We conclude that providing congruent information on a kicker's preferences positively impacts goalkeepers' anticipation. This confirms a model that expertise differences between experienced goalkeepers and novices are more prominent when the interaction of bottom-up and top-down processes is difficult.